Gender and power: Women’s leadership in the prevention and management of conflicts in Africa - Diallo, Boubacar Sidi (Wydawnictwo Naukowe UAM, 2015)
This paper describes the role and the place of the woman in African society, with particular focus on the issues of leadership, peace and security. Although women in Africa are more numerous than men, their position is not an enviable one. Thus this work will attempt to describe the causes which prevent the female kind from coming to the fore and being truly equal to men. In order to achieve that aim, one should consider the place of the woman, not only in the traditional society but also in what one sees as the contemporary realities of Africa. The author demonstrates that in most African countries, women had long been excluded from enjoying political rights, and that they have gained such entitlement only recently. Among the reasons which would account for this absence of women in the realm of leadership, one should draw attention to the patriarchal model of authority one acquires as a child and the burden of ancestral tradition which hinges upon the primacy of the male. There are also the additional burdens imposed over time by religions, which had always relegated the woman to the background.The woman has always been associated with the weaker sex, while being the one who gave life. The scope of this paper is limited to the presence of women in the public sphere, that is to say to their leadership in the affairs of peace and security, where women have or may have a certain influence. Certain difficulties encountered by African women with respect to leadership are also experienced by women in other parts of the world. With a few exceptions, all societies have been and continue to be governed by the same principles of exclusion. In Africa, just as everywhere else, there is no need for profound studies to conclude that feminist literature is not particularly abundant. This paper represents an exploration of a subject of no minor importance, namely the leadership of women in preventing and management of conflicts in Africa. Nevertheless, it is limited to a general view and does not analyse specific cases in each of the African countries.
Keywords: leadership; gender; man; woman; power; peace; security; conflicts; Africa